National Brands and Global Markets An Historical Perspective (Taylor & Francis, 2023)
Brands, Historical, Perspective, National, Markets, Global
English
Keywords: Economic history; Economics; Sales and marketing; Brands, Historical, Perspective, National, Markets, Global